2018
DOI: 10.1142/s0218127418500359
|View full text |Cite
|
Sign up to set email alerts
|

Hopf and Bautin Bifurcation in a Tritrophic Food Chain Model with Holling Functional Response Types III and IV

Abstract: In this paper, we analyze the Hopf and Bautin bifurcation of a given system of differential equations, corresponding to a tritrophic food chain model with Holling functional response types III and IV for the predator and superpredator, respectively. We distinguish two cases, when the prey has linear or logistic growth. In both cases we guarantee the existence of a limit cycle bifurcating from an equilibrium point in the positive octant of [Formula: see text]. In order to do so, for the Hopf bifurcation we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Banerjee and Das [24] have shown the impulsive effect on a tritrophic food chain model with mixed functional responses under seasonal perturbations. Castellonas et al [25] have shown both Hopf and Bautin bifurcations in a tritrophic food chain model. Huang et al [26] discussed the dynamical behavior of a food chain model with stage structure and time delays.…”
Section: Mathematical Modeling In Ecologymentioning
confidence: 99%
“…Banerjee and Das [24] have shown the impulsive effect on a tritrophic food chain model with mixed functional responses under seasonal perturbations. Castellonas et al [25] have shown both Hopf and Bautin bifurcations in a tritrophic food chain model. Huang et al [26] discussed the dynamical behavior of a food chain model with stage structure and time delays.…”
Section: Mathematical Modeling In Ecologymentioning
confidence: 99%
“…Proof. If the hypothesis are valid, using Proposition 2.2 for the transversality condition and the Kuznetsov formulae (see [2,7,8]) for the first Lyapunov coefficient, the Mathematica software allows to get by a direct calculation:…”
Section: Dynamics Of One Equilibrium Pointmentioning
confidence: 99%
“…Furthermore they analyzed and determined conditions in order to obtain a stable limit cycle in tritrophic models. These are systems in which three differential equations are involved, as they analyze the behavior of three species, prey, predator and superpredator ( Francoise and Llibre, 2011 , Castellanos et al, 2018 , Dawed et al, 2020 ) and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the analysis of the tritrophic models, the authors presented conditions in the parameters of the analyzed system, under which there exists a stable limit cycle for a system with a functional response of type Lotka Volterra or Holling. This was proved by showing the existence of a Hopf or a Bautin bifurcation ( Castellanos et al, 2018 , Bentounsi et al, 2018 , Blé et al, 2018 , Wang and Yu, 2019 , Dawed et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation